Estruturação da comunidade de Scarabaeinae em um gradiente de restauração de Floresta Atlântica - Audino, Lívia Dorneles (2015)
Restoration ecology is being considered an important strategy to reduce biodiversity loss and maintain ecosystem functions. Thus, it is necessary to know the real efficacy of this strategy in relation to the conservation and maintenance of different ecosystem components. Besides, it is important to find theoretical basis to support restoration practices. The general objective of the present thesis was to study dung beetle community assembly in an Atlantic Forest restoration chronosequence, determining whether the assembly trajectories converge or diverge from the reference and degraded systems and analyzing which factors are the main determinants of this assembly. So, we sampled dung beetles in 15 forest restoration areas of different ages and in five areas of primary forest, old secondary forest (reference systems) and introduced pastures (degraded system). Dung beetle communities were categorized according to functional trait diversity and composition. All restoration areas were measured in relation to its local environmental conditions (vegetation structure and soil), landscape context (forest cover percentage surrounding and distance to environmental reserves) and spatial patterns (PCNM’s). Restoration success was evaluated using measures of species diversity, composition and functional diversity. Our results show that restoration areas have the capacity to host forest-restricted species and are progressing towards the reference systems according to species composition similarity. However, species diversity and functional diversity was extremely low, presenting similar patterns to the ones found in pastures (starting point of the restoration). This demonstrates that 18 years was not enough to recover a diverse and stable dung beetle community. We also underscore the importance of utilizing more than one metric to characterize assemblages found in restored areas in order to better evaluate restoration success. Assembly of both species and functional trait composition were predominantly driven by niche-based processes, mainly by the influence of local environmental filters. Landscape and spatial descriptors had little or none independent contributions, presenting mostly shared effects with each other and local environment. Dung beetle dispersal is mostly determined by species specific environmental responses. However, the importance of stochastic factor cannot be completely rule out. We also document how these environment and landscape variables make the restoration areas more similar to the primary forest in relation to species and functional trait composition.